DOMINATION PARAMETERS OF POWER OF CENTIPEDE AND PN + KM - Prasad, G. Easwara (Journal of Global Research in Mathematical Archives(JGRMA), 2018)
The domination parameters of a graph Â of order Â has been already introduced. It is defined as Â is a dominating set of Â if every vertex Â is adjacent to atleast one vertex in Â In this paper, we have established various domination parameters ofÂ power of Centipede graph and Pn + KmÂ , also we haveÂ studied the relation between this parameters and illustrated with an examples. Keywords: Graph, Domination, Centipede, Path and null graph